Geographical distribution and evaluation of mosquito larvivorous potential of Aphanius dispar (Rüppell), a native fish of Gujarat, India - Sarfarazul Haq & Rajpal S. Yadav (Journal of Vector Borne Diseases, 2011)
Background & objectives: Certain indigenous fish can play potential role in vector control. The study recordeddistribution of Aphanius dispar (Rüppell) in its native habitats in Gujarat, India and evaluated its larval propensityfor Indian mosquito vectors.Methods: Fishes were surveyed in various districts of Gujarat and samples were collected from coastal habitatsand were identified to species. Physicochemical properties of water samples were analysed in the laboratory.Five laboratory acclimatized adult fish (2.2–3 cm) released in chlorine-free water in glass jars were providedwith 500 larvae daily. Five replicates were run. Daily consumption of I to IV instars of Anopheles stephensi,Aedes aegypti and Culex quinquefasciatus was recorded separately for three days. Anopheles stephensi larvalcontrol using the fish in industrial tanks (9–180 m2) was evaluated.Results & conclusion: The fish was found in large numbers in estuarine waters, rivulets, backwaters and smalldams in the districts of Kutch, Jamnagar, Patan and Anand in Gujarat. Mean daily consumption of larvae inlaboratory was as follows: An. stephensi 128 ± 0.2 to 204 ± 6; Cx. quinquefasciatus 24 ± 4 to 58 ± 10; Ae.aegypti 43 ± 5 to 68 ± 2. In water tanks, A. dispar reduced 93% larval counts by Day 7 and 98% by Day 21(p <0.01), showing high larval propensity. A consolidated information on bionomics, tolerance and physicochemicalproperties of water taken from natural habitats of A. dispar indicate its high larvivorous potential. Large-scaleevaluation is warranted to evaluate its potential in vector-borne disease control.